IMPROVING WRITING SKILL THROUGH FREE WRITING TECHNIQUE - Gufrana; Darmawan, Darmawan; Anggreni, Afrillia (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aimed to prove whether Free Writing Technique could improve the eighth-grade students' skills in writing descriptive text. The researcher used a quasi-experimental research design. The population of this research was the eighth-grade students at SMP Negeri 1 Dampal Selatan, consisting of 3 classes. The sample was chosen using a random sampling technique to select an experimental and control group. The samples were class VIII B as the experimental group and class VIII c as the control group. The pretest result showed that the experimental group's mean score was 47.91, while the control group's was 48.75. The mean score of the experimental group on the posttest was significantly improved from 47.91 to 76.25. Furthermore, the result of the data analysis showed that the t-counted value of 2.82 was higher than the t-table value of 2.02 by applying a 0.05 level of significance and 38 degrees of freedom. Therefore, the hypothesis of this research was accepted. In conclusion, the eighth-grade students' skill in writing descriptive text at SMP Negeri 1 Dampal Selatan can be improved through Free Writing Technique.